Impacto de los servicios de asistencia y protección social en la calidad de vida del adulto mayor residente en el hogar geriátrico fundación Esteban Quirola de la ciudad de Machala, provincia de El Oro año 2013 - Carpio Ibáñez, Anggie Yamilly (2015)
This research study corresponds to the Geriatric Home Foundation Esteban Quirola which is linked to service protection and social assistance for elderly people, who are acting as internal, whether under the method of pension monthly and other assisted free, to establish a range of problems that elderly residents face in the institution in question. The analysis focused research the various complications faced by older adults and the institution in general, such as: Lack of skilled professionals, lack of assessment of the current range of services, role delegation of responsibility to the nursing home. This study thesis entitled: "Impact of support services and social protection in the quality of life of the elderly resident Geriatric Home Foundation" Esteban Quirola "of the city of Machala, province of El Oro 2014" has as to determine the significance and objective social impact services assistance and protection to seniors who currently offer Geriatric Home "Foundation Esteban Quirola" city of Machala. The development of this research attempts to lay foundation for the nursing home can improve the provision of care services and social protection as well as improving institutional strategies to improve the well-being of the elderly. And last is very important to state that the information collected to authorities and human talent of the institution constituted an essential and valuable for the realization of this thesis contribution.